A Review on Latest Technologies in Big Data Analysis - S, Castro; R, Pushpalakshmi (International Journal of Engineering and Technology, 2018)
In this digital world, the modern information systems have produced a large amount of data which needs huge depositary in terms of terabytes for storage. Some of the digital technologies such as cloud computing and Internet of Things (IoT) are considered as the major sources of such large data. It is necessary to extract knowledge by analyzing these huge data which needs several attempts at multiple stages for decision making. Thus, the recent researches have focused on the analysis of big data. The main aim of this paper is to investigate the challenges of big data, applications, opportunities, implantation tools and its research problems. Thus, this study presents a platform to investigate big data at various levels. Moreover, it initiates a novel perspective for researchers to provide the solutions according to the challenges and research problems.Â